Controllable nano-fibrous interlayers for improved thermal insulation performance. (October 2020) - Liang, Yuying; Wang, Yangjun; Wu, Huijun; Huang, Gongsheng; Yang, Jianming
Highlights: Nano-fibrous interlayers are incorporated into battings to improve thermal insulation. Heat transfer models of battings with interlayers are developed and validated. The interlayer with a 2.0 vol% content is best in thermal insulation. Thermal insulation is improved by 10.0% through controllable design of interlayers. Abstract: Nano-fibrous interlayers exhibit extensive prospects in improving the thermal insulation performance of porous media owing to their strong radiative extinction. However, the traditional two-flux method for predicting the thermal performance of micro-scale battings may produce large deviations because of the nano-scale diameter of interlayers. This study is thus to develop an effective heat transfer model by combining the Mie scattering theory and two-flux model to predict the thermal performance of battings with nano-fibrous interlayers. Nano-fibrous interlayers with a 0.5 mm thickness and a 500 nm diameter were prepared via electrospinning techniques, and those with various layer numbers were incorporated into battings. A test platform was established to measure their heat flows. The modelling results were compared with the measured ones for validations. The heat transfer mechanism was studied for varying fibre contents, layer numbers and thicknesses of interlayers. The results suggested that the radiative heat flow was significantly decreased, whereas the variation of conductive heat flow was determined by the controllable parametric design. Through the controllable design of nano-fibrous interlayers, the total thermal insulation performance could be increased by 10.0% with the insignificant change of the weight. This study could provide guidance in the controllable design of nano-fibrous interlayers for improving the thermal performance of fibrous insulation.